Tanjungbalai City Government Responsibilities in Managing Coastal Fisheries - Ramlan Ramlan (International Journal Reglement & Society (IJRS), 2022)
Regulatory issues in the management of marine and fishery areas between Law Number 23 of 2014 concerning Regional Government and Law Number 1 of 2014 concerning Amendments to Law Number 27 of 2007 concerning Management of Coastal Areas and Small Islands will have an impact on effectiveness fisheries management, including the local government of Tanjungbalai City in managing fisheries in its coastal areas. The authority of the Tanjungbalai City Regional Government in managing marine and fishery resources in the Tanjungbalai coastal area is based more on Article 25 A and Article 45 of the Law of the Republic of Indonesia Number 45 of 2009 concerning Amendments to Law Number 31 of 2004 concerning Fisheries and Article 14 of the Law -Law Number 1 of 2014 concerning Amendments to Law Number 27 of 2007 concerning Management of Coastal Areas and Small Islands. The obstacles faced by the Tanjungbalai regional government in managing the Tanjungbalai coastal area are the withdrawal of the authority for marine fisheries management to the provincial government, causing the Tanjungbalai Regional Government to experience a decrease in regional income from the fisheries sector